Perbandingan Yahwe dalam Perjanjian Lama dan Lera Wulang Tanah Ekang dalam Budaya Tenawahang - Yohanes Jemiandro Bala Kelen (Divinitas Jurnal Filsafat dan Teologi Kontekstual, 2026)
This study examines the comparison of the concept of divinity in two cultures, Yahwe in the Old Testament and Lera Wulang Tanah Ekang in the Tenawahang culture. Based on textual and contextual analysis, this study explores the possible relationship between the concept of divinity in Israeli culture and Tenawahang culture. The purpose of this study is to identify the similarities and differences between the concept of divinity in the Old Testament and that in Tenawahang culture. The analytical method used in this study is a comparative descriptive analysis of Yahwe in the Old Testament and Lera Wulang Tanah Ekang in Tenawahang culture. The author collected data using the literature method to examine the concept of divinity in the Old Testament and the field method with interview techniques and the author's experience to examine the concept of divinity in Tenawahang culture. This article examines the comparison of the concept of divinity between the two cultures by seeking similarities and differences between them and conducting a synthesis analysis. Finally, the author found similarities and differences in the concept of divinity in these two cultures. The results of this study indicate that there are similarities between the concept of divinity in the Old Testament and Tenawahang culture. Both the Old Testament and Tenawahang culture adhere to monotheism, a relationship with humanity, and a reverence for life. The differences between the Old Testament and Tenawahang culture lie in names and representations, doctrines and laws, and the concept of the chosen people.AbstrakPenelitian ini mengkaji perbandingan konsep ketuhanan dalam dua budaya, Yahwe dalam Perjanjian Lama dan Lera Wulang Tanah Ekang dalam budaya Tenawahang. Berdasarkan analisis tekstual dan kontekstual, penelitian ini mengeksplorasi kemungkinan hubungan konsep Ketuhanan dalam budaya Israel dan budaya Tenawahang. Tujuan dari penelitian ini adalah untuk mengetahui persamaan dan perbedaan konsep Ketuhanan dalam Perjanjian Lama dengan budaya Tenawahang. Metode analisis yang digunakan dalam penelitian adalah metode analisis deskriptif komparatif terhadap Yahwe dalam Perjanjian Lama dan Lera Wulang Tanah Ekang dalam budaya Tenawahang. Penulis mengumpulkan data dengan menggunakan metode pustaka untuk melihat konsep ketuhanan dalam Perjanjian Lama dan metode lapangan dengan teknik wawancara serta pengalaman penulis untuk melihat konsep ketuhanan dalam budaya Tenawahang. Artikel ini mengkaji perbandingan konsep ketuhanan terhadap kedua budaya tersebut dengan mencari persamaan dan perbedaan di antara keduanya dan melakukan analisis sintesis. Akhirnya penulis menemukan ada persamaan dan perbedaan konsep ketuhanan dalam kedua budaya ini. Hasil dari penelitian ini adalah bahwa ada persamaan antara konsep ketuhanan Perjanjian Lama dan budaya Tenahawang. Perjanjian Lama dan budaya Tenahawang sama-sama menganut monoteisme, relasi dengan manusia, dan adanya penghargaan terhadap hidup. Sedangkan perbedaan Perjanjian Lama dan budaya Tenahawang terletak pada nama dan representasi, doktrin dan hukum, serta konsep tentang umat pilihan.